Investigating the Effect Model of Defense Mechanisms and Coping Skills on Entrance Exam Anxiety in Adolescent Girls with Generalized Anxiety Disorder (GAD) with the Mediating Role of Resilience - Almasian, Hanie; Bayat, Mina; Abdi, Sara; Zakerin, Sara; Kazemi, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aims to examine how defense mechanisms and coping strategies influence entrance exam anxiety in adolescent girls with generalized anxiety disorder, with a focus on the mediating role of resilience.Methodology: The present study falls under the category of descriptive-correlational research and utilizes a cross-sectional research design, employing structural equation modeling (SEM) and mediating variable analysis. The statistical population for this study consisted of all adolescent girls with generalized anxiety disorder (GAD) at the pre-university level in Tehran from May to November 2024. A sample of 141 adolescent girls was selected using purposive sampling. The research instruments used include the coping strategies questionnaire (CSQ), Connor-Davidson Resilience Scale (CD-RISC), defense style questionnaire (DSQ-40), and Test Anxiety Questionnaire (TAQ). Data analysis was performed with SPSS version 27 and Smart PLS 4 software, applying the structural equation model method. Statistical analysis was conducted using a P-value of 0.05.Findings: The research results showed that problem-solving by being resilient had a notable adverse effect on exam anxiety (β=-0.053, P=0.040). Having an Immature defensive style was also found to boost exam anxiety through resilience, as indicated by a noteworthy positive impact (β=-0.067, P=0.010). It is evident that by increasing resilience, individuals can lessen the impact of an immature defensive style on exam anxiety. The study revealed that the problem-solving significantly increased resilience with a beta coefficient of 0.187 and p-value of 0.022. On the other hand, the emotional restraint aspect had a significant negative impact on anxiety (β=-0.308, p=0.000). Attracting social support was discovered to have a notable adverse effect on anxiety, according to the study findings (β=-0.129, P=0.047).Conclusion: The results of this study demonstrated that enhancing coping mechanisms, immature defensive style, and building resilience can be beneficial in assisting students dealing with anxiety during entrance exams, with mental resilience being a key focus for interventions aimed at enhancing mental well-being.Purpose: This study aims to examine how defense mechanisms and coping strategies influence entrance exam anxiety in adolescent girls with generalized anxiety disorder, with a focus on the mediating role of resilience.Methodology: The present study falls under the category of descriptive-correlational research and utilizes a cross-sectional research design, employing structural equation modeling (SEM) and mediating variable analysis. The statistical population for this study consisted of all adolescent girls with generalized anxiety disorder (GAD) at the pre-university level in Tehran from May to November 2024. A sample of 141 adolescent girls was selected using purposive sampling. The research instruments used include the coping strategies questionnaire (CSQ), Connor-Davidson Resilience Scale (CD-RISC), defense style questionnaire (DSQ-40), and Test Anxiety Questionnaire (TAQ). Data analysis was performed with SPSS version 27 and Smart PLS 4 software, applying the structural equation model method. Statistical analysis was conducted using a P-value of 0.05.Findings: The research results showed that problem-solving by being resilient had a notable adverse effect on exam anxiety (β=-0.053, P=0.040). Having an Immature defensive style was also found to boost exam anxiety through resilience, as indicated by a noteworthy positive impact (β=-0.067, P=0.010). It is evident that by increasing resilience, individuals can lessen the impact of an immature defensive style on exam anxiety. The study revealed that the problem-solving significantly increased resilience with a beta coefficient of 0.187 and p-value of 0.022. On the other hand, the emotional restraint aspect had a significant negative impact on anxiety (β=-0.308, p=0.000). Attracting social support was discovered to have a notable adverse effect on anxiety, according to the study findings (β=-0.129, P=0.047).Conclusion: The results of this study demonstrated that enhancing coping mechanisms, immature defensive style, and building resilience can be beneficial in assisting students dealing with anxiety during entrance exams, with mental resilience being a key focus for interventions aimed at enhancing mental well-being.